Ocena pracy przydomowych oczyszczalni ścieków bio-duo w pierwszych miesiącach eksploatacji = Evaluation sewage treatment plants bio-duo in the first months of operation - Jakubaszek, Anita; Stadnik, Artur (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article presents the results of the basic indicators of pollutants in sewage from domestic wastewater treatment plants BIO-DUO company Sotralentz. Research sewage treatment facilities were located in the Dolnośląskie Province in the municipality of Bardo. The study was conducted in the first half operation of facilities. We analyzed effluent discharged into the receivers, which are cesspools or drainage ditches.
Keywords: oczyszczanie ścieków; przydomowe oczyszczalnie ścieków; wastewater treatment; sewage treatment plants